Design Of A Microsoft Access-Based Accounting And Internal Control System At Pasti Jaya Store - Supriyanto Supriyanto; Resnika Resnika (ConCEPt - Conference on Community Engagement Project, 2023)
The aim of this project is to provide an accurate, systematic, and reliable accounting recording system according to the needs of Toko Pasti Jaya. Toko Pasti Jaya is an individual business unit with an MSME scale (Micro, Small and Medium Enterprises) in the retail trade sector of basic commodities. The store's accounting records are still carried out using a simple bookkeeping method without an adequate and organized accounting system. In addition, the related business also does not design an efficient and effective internal control system. The implementation phase of the project is carried out by analyzing the needs of the internal control system and accounting records of business through interviews and observations. The design of databases and programs with Microsoft Access is done according to the necessities of owner. The output of the implementation phase is the presentation of a user-friendly accounting program for partners. This project contributes to designing a platform that can support the efficiency and effectiveness of business operations in accordance with the vision, mission and business objectives of Pasti Jaya Store.